Kesiapan UMKM dalam Mengimplementasikan Digitalisasi Ekonomi - Reyhan Yusuf Almer; Negina Kencono Putri (Department of Accounting-Faculty of Economic and Business (FEB), 2022)
The purpose of this research is to find out whether Micro Small and Medium Enterprises (MSME) actors are ready to implement the digitization of financial statements. The subjects in this study were MSMEs in South Tangerang City which were registered with the Cooperatives and MSMEs Service in South Tangerang City. The data is taken from the results of interviews, observations and documentation. Data analysis used 4 stages: data collection, data reduction, data presentation and drawing conclusions. The results of this study are the South Tangerang City MSMEs are ready to implement the digitization of financial reports. and already have sufficient knowledge in implementing the digitization of financial reports. However, MSMEs still encounter obstacles in implementing the digitization of financial reports. The implication of this research is that the Department of Cooperatives and SMEs in South Tangerang City can continue to provide education to MSMEs in South Tangerang City regarding the implementation of digitizing financial reports.